Rekonstruksi Restoratif Justice Dalam Pemberantasan Korupsi: Membangun Keadilan Menuju Indonesia Emas 2045 - Faisal, Fitriah; Nur, Fuad; Pratama, Aman; Handrawan, Handrawan (Jurnal Hukum IUS QUIA IUSTUM, 2025)
The urgency of this research is highly necessary in order to alter the paradigm of corruption criminalisation based on punishment towards recovery. The formulation of the problem in this research is whether the shift in the spirit of corruption criminalization from retributive justice to restorative justice can guarantee the realisation of national economic recovery towards the Indonesia Emas 2045 vision and how the reconstruction of restorative justice through the approach of categorizing state losses in the criminalization system in Indonesia. This research uses a normative legal research type that is prescriptive. The results of this study indicated that (1) The teachings of retributive justice in legal practice in other countries such as the Netherlands have been abandoned and adopted the teachings of restorative justice. This teaching is in line with the ideology of Pancasila, so it is very important to be applied in the corruption criminalization system in Indonesia. (2) Restorative justice reconstruction based on state loss categories includes: Category 1 state losses below 200 million plus 1/4, Category 2 state losses of at least 200 million to a maximum of 1 billion plus 1/3, Category 3 state losses of at least 1 billion and a maximum of 5 billion plus 1/2, Category 4 state losses of 5 billion but not more than 100 billion plus 2/3, Category 5 state losses above 100 billion plus 100%. This study concluded that the restorative justice categorisation approach in handling corruption cases will realize efforts to restore the national economy towards the Indonesia Emas 2045 vision.